Demografic analysis of biopesticide effects on the two-spotted spider mite (Acari: Tetranychidae) following egg treatment - Međo Irena (Pesticidi i Fitomedicina)
The effects of biopesticide products based on oxymatrine, azadirachtin and Beauveria bassiana (strain ATCC 74040) on demographic parameters of the two-spotted spider mite, Tetranychus urticaeKoch (Acari: Tetranychidae), were evaluated in laboratory bioassays. The biopesticides were applied by spraying 24 h old eggs laid on bean leaves, using the following concentrations: 50 pl/l (oxymatrine-based product), 0.75 g/l (azadirachtin-based product) and 3 ml/l (B. bassiana-based product). These concentrations were within 95% confidence limits of the LC50s estimated in acute toxicity bioassays. The mites that hatched from treated eggs completed their juvenile development on the same leaf discs, i.e. the toxic effect was caused by topical treatment and residual exposure. When the surviving females entered their preovipositional period, cohorts of 40 control and 40 treated females were transferred to untreated leaf discs (1 female/disc). Females were transferred daily to new discs until the death of the last one. Using the data on their age-specific survival and age-specific fertility (production of fem ale offspring), the following dem ographic parameters were estimated: gross reproductive rate (GRR), net reproductive rate (R0), intrinsic rate of increase (rm), finite rate of increase (A), and mean generation time (T). The biopesticides significantly affected these dem ographic parameters in fem ales that survived treatm ents. All three biopesticides significantly reduced the GRR and R0values. In the bioassays with oxymatrine-and azadirachtin-based products, the rm and A values were reduced by 22% and 5%, and 16% and 4%, respectively, due to reduced survival and fertility, as well as extended juvenile developmental time of females that survived treatment, compared to control females. In the bioassay with the B. bassiana-based product, the rm and A values were reduced by 7% and 2%, respectively, mostly due to the reduced survival of treated females. The oxymatrine-and azadirachtin-based products significantly extended, while B. bassiana-based product reduced the T values.